Indian migrations - Warner, Rachel (Wayland, Hove, 1994)
"Indian Migrations" by Rachel Warner, published in 1994. This 48-page work examines the history of migration from India, exploring the reasons behind these movements and the experiences of Indian migrants in their new countries. It delves into the socio-economic and political factors that have influenced Indian migration patterns over time. Given its publication date, the book provides historical context up to the early 1990s. For more recent information on Indian migration trends, additional sources would be beneficial.